Restriction endonuclease BsoFI is sensitive to the 5'-methylation of deoxycytidines in its recognition sequence. - Deissler, H (1995)
The isoschizomeric restriction endonucleases Fnu4HI and BsoFI cleave DNA at 5'-GCdecreasesNGC-3' sequences. Fnu4HI has been shown to be inhibited by 5'-CG-3'methylation in the sequences 5'-GmCGGC-3' or 5'-GCGGmCG-3'. We have now investigated the methylation sensitivity of BsoFI by testing its activity on plasmid DNA 5'-CG-3' methylated with the M.SssI DNA methyltransferase or on synthetic (CGG)n repetitive oligodeoxyribonucleotides which have been partly or completely C methylated. The data demonstrate that BsoFI cannot cleave at its recognition sequence when it is completely 5'-CG-3' methylated. These enzymes have proven to be useful in analyses of the methylation status in (CGG)n repeats of the human genome.